Subclinical Hypothyroidism and Depression: A Systematic Review and Meta-Analysis - Tang, Rong; Wang, Jian; Yang, Lili; Ding, Xiaohong; Zhong, Yufan; Pan, Jiexue; Yang, Haiyan; Mu, Liangshan; Chen, Xia; Chen, Zimiao (Frontiers in Endocrinology, 2019)
Background: Thyroid function is closely associated with neuropsychological functions, including mental state and cognitive functions. Although thyroid function is routinely examined in persons with depressive symptom, the association between subclinical hypothyroidism (SCH) and depression remains inconclusive. Objective: This systematic review and meta-analysis aimed to evaluate the risk of depression in persons with SCH. Methods: The PubMed, Embase, and Web of Science databases were searched up to August 2018. The primary outcome was the prevalence of depression, as evaluated by various types of self-reported depression scales. Odds ratios (ORs) were calculated to compare the risk of depression between persons with SCH and those with euthyroidism. Results: Twenty-one studies were included in the systematic review, with a total of 103,375 subjects from 7 studies being pooled for the meta-analysis to evaluate the risk of depression. The meta-analysis showed that persons with SCH had a significantly elevated risk of depression than persons with euthyroidism (OR = 1.78, 95% confidence interval [CI]: 1.11–2.86, P = 0.02). No publication bias was found, as indicated by Egger's test (t = −0.49, P = 0.647) and Begg's test (z = −0.15, P = 0.881). In addition, the funnel plot showed a symmetric distribution. Conclusions: This meta-analysis demonstrated that SCH was positively associated with the risk of depression, especially in persons above 50 years of age, suggesting it is necessary to pay close attention to depressive symptoms in persons with SCH.